Source and fate of dissolved inorganic carbon in Jiulong River, southeastern China. (5th November 2020) - Yin, Xijie; Lin, Yunpeng; Liang, Cuicui; Tao, Shuqin; Wang, Liang; Xu, Yonghang; Li, Yunhai
Abstract: In this study, surface water samples were collected over several seasons from the Jiulong River mainstream (North and West Rivers) and estuary from 2013 to 2014. The concentration of dissolved inorganic carbon (DIC), stable carbon isotope composition (δ 13 CDIC ), in-situ temperature, pH, and conductivity of the surface water were measured to study the source and fate of DIC in the Jiulong River. The results showed that the DIC concentrations decreased from upstream to downstream in the North River but increased in the West River, which was determined mainly by the lithology of the drainage basin. In spring, the river is fed by deep groundwater resources that are older and contain more DIC originating from carbonate weathering compared to surface water, resulting in the high concentration and δ 13 CDIC value of DIC. Whereas during the summer and autumn, the high runoff caused by frequent precipitation dilutes the DIC concentration of river water and the contribution of soil CO2 is more important, resulting in lower DIC concentration and δ 13 CDIC value. δ 13 CDIC values indicate that the DIC in the Jiulong River was derived mainly from the chemical weathering of bedrock, and CO2 outgassing was one of the main fates of the riverine DIC. Results of mixing ratio calculation in freshwater and seawater suggest that additional processes existed with the mixing process, which were identified as organic carbon degradation and respiration in summer and autumn and offshore water vertical mixing in winter and spring, but in general the spatial variation of DIC in the estuary was determined mainly by mixing of freshwater and seawater. This study complements our understanding of the sources and fates of DIC in small river systems on the continental margin of the East China Sea. Highlights: Riverine DIC content was determined by the lithology of the basin in Jiulong River. CO2 outgassing is one of the main fates of riverine DIC. Significant seasonal variation of riverine DIC was found in Jiulong River. Riverine DIC and marine DIC are not conservative mixed in the estuary. Organic carbon degradation is the main additional process of DIC in the estuary.